2021
DOI: 10.1001/jama.2021.4502
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones in Pregnancy

Abstract: The risk of developing gallstones can increase during pregnancy.The main purpose of the gallbladder is to store bile, which is released into the small intestine after meals to help with digestion. Bile is made up of cholesterol, bilirubin (a product of red blood cells), and bile salts. Gallstones are formed when these components are not well balanced.Women are at higher risk of gallstones, and that risk increases during pregnancy. Increased hormones during pregnancy can cause higher cholesterol levels and dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Unlike previous reports, a higher prevalence of gallstones among men was observed in this study. Several classic epidemiologic studies have reported that pregnancy and female sex hormones place women at a higher risk [36]. The high prevalence of gallstones among men in our study population is an indicator of a significant shift in the epidemiology of gallstone disease.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Unlike previous reports, a higher prevalence of gallstones among men was observed in this study. Several classic epidemiologic studies have reported that pregnancy and female sex hormones place women at a higher risk [36]. The high prevalence of gallstones among men in our study population is an indicator of a significant shift in the epidemiology of gallstone disease.…”
Section: Discussionmentioning
confidence: 65%
“…Established risk factors for the development of cholesterol gallstones due to enhanced cholesterol synthesis and secretion include genetic background and lifestyle, as well as internal disorders such as aging, female sex, pregnancy, obesity, rapid weight loss, diabetes mellitus, and dyslipidemia [5][6][7][8][9][10]. Predominant risk factors for pigment stones include liver dysfunction [11], Crohn's disease [12], and hyperbilirubinemia due to underlying genetic predisposition [13].…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal changes during pregnancy may predispose patients to gallstone formation [ 9 ]. The literature estimates a 0.01–0.06% incidence of cholecystitis during pregnancy, though modern data are lacking [ 10 ].…”
Section: Description Of the Health Problemsmentioning
confidence: 99%
“…Unlike previous reports, a higher prevalence of gallstones among men was observed in this study. Several classic epidemiologic studies have reported that pregnancy and female sex hormones place women at a higher risk [3][4][5][6]. The high prevalence of gallstones among men in…”
Section: Plos Onementioning
confidence: 99%
“…A variety of risk factors have been reported to be associated with gallstone formation. Established risk factors for the development of cholesterol gallstones due to enhanced cholesterol synthesis and secretion include genetic background and lifestyle, as well as internal disorders such as aging, female sex, pregnancy, obesity, rapid weight loss, diabetes mellitus, and dyslipidemia [5][6][7][8][9][10]. Predominant risk factors for pigment stones include liver dysfunction [11], Crohn's disease [12], and hyperbilirubinemia due to underlying genetic predisposition [13].…”
Section: Introductionmentioning
confidence: 99%